Using quantitative tissue phenotype to assess the margins of surgical samples from a pan‐Canadian surgery study. Issue 6 (16th February 2018) - Guillaud, Martial; MacAulay, Calum E.; Berean, Kenneth W.; Bullock, Martin; Guggisberg, Kelly; Klieb, Hagen; Puttagunta, Lakshmi; Penner, Carla; Kwan, Keith; Rosin, Miriam P.; Poh, Catherine F.
Abstract: Background: The purpose of this study was to use quantitative tissue phenotype (QTP) to assess the surgical margins to examine if a fluorescence visualization‐guided surgical approach produces a shift in the surgical field by sparing normal tissue while catching high‐risk tissue. Methods: Using our QTP to calculate the degree of nuclear chromatin abnormalities, Nuclear Phenotypic Score (NPS), we analyzed 1290 biopsy specimens taken from surgical samples of 248 patients enrolled in the Efficacy of Optically‐guided Surgery in the Management of Early‐staged Oral Cancer (COOLS) trial. Multiple margin specimens were collected from each surgical specimen according to the presence of fluorescence visualization alterations and the distance to the surgical margins. Results: The NPS in fluorescence visualization‐altered (fluorescence visualization‐positive) samples was significantly higher than that in fluorescence visualization‐retained (fluorescence visualization‐negative) samples. There was a constant trend of decreasing NPS of margin samples from non‐adjacent‐fluorescence visualization margins to adjacent‐fluorescence visualization margins. Conclusion: Our results suggested that using fluorescence visualization to guide surgery has the potential to spare more normal tissue at surgical margins.